’'Se on semmoinen juttu, mitä odottaa’’ : MS-tautia sairastavien kokemuksia ratsastusterapiasta - Lukkaroinen, Anne-Mari (2023)
Hippotherapy is a form of rehabilitation that utilizes the movements produced by a horse to elicit sensory and motor responses. Hippotherapy is commonly used in the rehabilitation of neurological diseases and disorders, and in Finland it is eligible for reimbursement by the Social Insurance Institution of Finland (Kela). Hippotherapy is widely employed in the rehabilitation of individuals with multiple sclerosis (MS) due to its potential positive effects on walking, balance, and spasticity, as supported by research findings. The aim of this Master's thesis is to explore the experiences of individuals with MS regarding hippotherapy and to enhance understanding of the significance of these experiences. This qualitative study was conducted as an interview study, utilizing a hermeneutic phenomenological methodology. The research data was collected by interviewing six (n=6) individuals with MS their experiences with hippotherapy. The interviews were conducted as semi-structured interviews through the Zoom conferencing application. The transcribed data from the interviews was analyzed using the hermeneutic phenomenological analysis method known as Interpretative Phenomenological Analysis (IPA). The results of the study revealed three overarching themes: factors influencing the accessibility of hippotherapy, psychological and physical effects of hippotherapy on wellbeing and meaningfulness of hippotherapy as a rehabilitation modality. Under these overarching themes, eight subthemes emerged. Applying for hippotherapy was perceived as challenging, and there was a negative atmosphere surrounding the application process. Additionally, those who received hippotherapy felt fortunate as it is a difficult-to-access form of therapy. The limited number of therapists offering hippotherapy and the resources they offer were also perceived as factors affecting accessibility. Hippotherapy was perceived to bring psychological and physical well-being, allowing individuals to escape from everyday concerns and thoughts related to reduced functional abilities. It provided nature experiences, increased a sense of empowerment, and its benefits extended to other aspects of life as well. The physical effects of hippotherapy were most notably observed in walking ability, balance, posture, and it also had perceived impacts on improving spasticity and bladder control. Hippotherapy was considered a meaningful form of rehabilitation and a targeted treatment for the symptoms of MS, and according to the experiences of the interviewees, it cannot be replaced by other therapeutic methods. It was also perceived as a more effective form of rehabilitation, and when combined with physiotherapy, complements the rehabilitation process of individuals with MS. Therapy horses were experienced as meaningful and essential components of equine therapy, and the dimension brought by their living presence in therapy cannot be replaced by mechanical means. The results of this study contribute to the understanding of how individuals with MS perceive hippotherapy, and recognition significance of hippotherapy as a meaningful rehabilitation modality. The research results may be utilized in the development of the rehabilitation pathway for individuals with MS, as well as in improving the implementation and accessibility of hippotherapy.